Ovarian cancer symptom awareness and anticipated time to help-seeking for symptoms among UK women. Issue 3 (24th May 2013) - Low, Emma L; Waller, Jo; Menon, Usha; Jones, Annwen; Reid, Frances; Simon, Alice E
Abstract : Objectives: To determine levels of awareness of ovarian cancer symptoms and to identify barriers to help-seeking and predictors of a longer time to help-seeking in a UK female population-based sample. Methods: A UK population-based sample of women [ n= 1000, including a subsample of women at higher risk due to their age (≥45 years, n =510)] completed the Ovarian Cancer Awareness Measure by telephone interview. Questions measured symptom awareness (using recall and recognition), barriers to medical help-seeking and anticipated time to help-seeking. Regression analyses identified predictors of a higher score on a scale of anticipated time to help-seeking. Results: Most women (58% overall sample; 54% subgroup) were unable to recall any symptoms but 99% recognised at least one. Recognition was lowest for difficulty eating and persistently feeling full. In the sample overall, higher socio-economic status and higher endorsement of practical and service barriers independently predicted a longer anticipated time to help-seeking for more symptoms. White ethnicity was an additional predictor in the older subgroup. Conclusions: This study suggests awareness of ovarian cancer symptoms is low in the UK, and varies widely between symptoms. It identifies variables that may be involved in a longer time to help-seeking for possible ovarian cancer symptoms and highlights the need for more in-depth research into the factors related to time to help-seeking in real-world situations.